Effect of Combined Single-Injection Femoral Nerve Block and Patient-Controlled Epidural Analgesia in Patients Undergoing Total Knee Replacement - Lee, Ae-Ryung (Yonsei University College of Medicine, 2011)
PURPOSE: Total knee replacement is one of the most painful orthopedic procedures, and effective pain relief is essential for early mobility and discharge from hospital. The aim of this study was to evaluate whether addition of single-injection femoral nerve block to epidural analgesia would provide better postoperative pain control, compared to epidural analgesia alone, after total knee replacement. MATERIALS AND METHODS: Thirty-eight patients received a single-injection femoral nerve block with 0.25% levobupivacaine (30 mL) combined with epidural analgesia (femoral nerve block group) and 40 patients received epidural analgesia alone (control group). Pain intensity and volume of patient-controlled epidural analgesia medication and rescue analgesic requirements were measured in the first 48 hours after surgery at three time periods; 0-6 hours, 6-24 hours, and 24-48 hours. Also, side effects such as nausea, vomiting, and pruritus were evaluated. RESULTS: Median visual analog scale at rest and movement was significantly lower until 48 hours in the femoral nerve block group. Patient-controlled epidural analgesia volume was significantly lower throughout the study period, however, rescue analgesia requirements were significantly lower only up to 6 hours in the femoral nerve block group. The incidences of nausea and vomiting and rescue antiemetic requirement were significantly lower in the femoral nerve block group up to 6 hours. CONCLUSION: The combination of femoral nerve block with epidural analgesia is an effective pain management regimen in patients undergoing unilateral total knee replacement.